2016
DOI: 10.1530/joe-16-0111
|View full text |Cite
|
Sign up to set email alerts
|

Precise expression of Fis1 is important for glucose responsiveness of beta cells

Abstract: Mitochondrial network functionality is vital for glucose-stimulated insulin secretion in pancreatic beta cells. Altered mitochondrial dynamics in pancreatic beta cells are thought to trigger the development of type 2 diabetes mellitus. Fission protein 1 (Fis1) might be a key player in this process. Thus, the aim of this study was to investigate mitochondrial morphology in dependence of beta cell function, after knockdown and overexpression of Fis1. We demonstrate that glucose-unresponsive cells with impaired g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 47 publications
1
20
0
1
Order By: Relevance
“…Type 2 diabetes was related to mitochondrial network fragmentation in myocardium and a large decrease in mfn1 expression. In another study, Schultz et al have confirmed that FIS1 is a key regulator in pancreatic β-cells [67] ; the authors found that both glucose-stimulated insulin secretion and mitochondrial dynamics were clearly adapted to produce precise expression levels of this fission protein.…”
Section: Type 2 Diabetes and Mitochondrial Dynamicsmentioning
confidence: 90%
“…Type 2 diabetes was related to mitochondrial network fragmentation in myocardium and a large decrease in mfn1 expression. In another study, Schultz et al have confirmed that FIS1 is a key regulator in pancreatic β-cells [67] ; the authors found that both glucose-stimulated insulin secretion and mitochondrial dynamics were clearly adapted to produce precise expression levels of this fission protein.…”
Section: Type 2 Diabetes and Mitochondrial Dynamicsmentioning
confidence: 90%
“…MtDNA copy number in β-cells lacking Opa1 is unchanged, but the activity of complex IV is significantly decreased, perturbing glucose-stimulated ATP production and GSIS (Zhang et al 2011). It was found that glucose-unresponsive cells exhibit poorer mitochondrial dynamics than glucose-responsive cells (Schultz et al 2016). Overexpression of FIS1 in glucose-unresponsive cells restores GSIS, and the mitochondrial network becomes more homogeneous.…”
Section: Figurementioning
confidence: 99%
“…Overexpression of FIS1 in glucose-unresponsive cells restores GSIS, and the mitochondrial network becomes more homogeneous. In contrast, silencing of Fis1 in murine insulin-secreting cells lessens glucose responsiveness and a higher frequency of elongated, likely dysfunctional, mitochondria is encountered (Schultz et al 2016). The prohibitin proteins have also been suggested to play important roles in maintaining mitochondrial integrity and function.…”
Section: Figurementioning
confidence: 99%
“…dass das Dynamin related protein 1 (Drp1) [13] und das Fission protein 1 (Fis1) [14], beides Proteine, die für die Teilung von Mitochondrien notwendig sind, in Beta-Zellen eine wesentliche Rolle spielen. Die Reduktion der Expression der genannten Proteine führte in Beta-Zellen nicht nur zu einer Strukturveränderung des mitochondrialen Netzwerks mit langen, ringförmigen und aggregierten Mitochondrien, sondern auch zu einer signifikanten Abnahme der glukoseinduzierten Insulinsekretion [13,14]. Neueste Ergebnisse deuten darauf hin, dass das mitochondriale Netzwerk einer Beta-Zelle auch dessen Glukose-Responsivität widerspiegelt [14].…”
Section: Abstract ▼unclassified